Asymmetric Synthesis of 2-Arylpyrrolidines by Cationic Cyclization - Coldham, Iain; Robinson, Steven P.; Baxter, Carl A. (Synlett, 2012)
Homoallylic amines were prepared by asymmetric deprotonation of benzylamines using n-BuLi and (–)-sparteine to give chiral organolithiums to which were added prenyl bromide. Removal of the Boc protecting group gave anilines that were found to undergo Brønsted acid catalyzed or iodine-mediated cyclization to give aryl-substituted pyrrolidine heterocyclic products with high enantioselectivity.
Keywords: amines; carbocation; cyclization; enantioselectivity; heterocycles